Upaya Meningkatkan Kemampuan Sosial Emosional Anak Melalui Metode Proyek Pada Kelompok B4 Di TK Al Islam 1 Jamsaren Surakarta Tahun Pelajaran 2014/2015 - ARDHYAN, Aulia Hasna, Dra. Surtikanti, S.H., M.Pd (2015)
Project method is one way of giving a learning experience by bringing the children to face day-to-day problems to be solved in groups. This can increase the child's emotional social abilities. In a learning proces the teacher was not optimal, because it was still glued to the magazine. The purpose of this research was to improve the social skills of emotional child in the kindergarten group B4 at Al Islam 1 Jamsaren Surakarta Academic Year 2014/2015. This research is a classroom action research (CAR) with 2 cycles work process consists of four stages, namely planning, action, observation, and reflection. The subjects were teachers and 30 children of B4 Al Islam kindergarten 1 Jamsaren. The study stateed that the project method could increase the children emotional social ability. The average percentage of a children abilities before the action until the second cycle were that the cycle was 37.8%, Cycle I62.3%, Cycle II 86.2%. The conclusion of this study was that there was ability of emotional social project method in TK Al Islam 1 Jamsaren Surakarta Academic Year 2014/2015.